2016
DOI: 10.1515/aoas-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and Molecular Diagnostics of XX/XY Chimerism in Cattle, Sheep, and Goats – A Review

Abstract: animal cell chimerism denotes the presence of two or more cell lines of different genetic origin. the most common form of chimerism, which occurs spontaneously in mammals, is the presence of two or more cell populations in animals derived from dizygotic twin or multiple pregnancies. the aim of this review is to present extensive information on XX/Xy chimerism in cattle, sheep and goats from the Bovidae family. additionally, it will discuss a methodology for a quick and accurate diagnosis of cell chimerism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 2 publications
0
16
0
2
Order By: Relevance
“…Current results indicate that slight H-Y antigen would not hamper reproduction of a heterosexual twin female. The presence of H-Y antigen in fertile heterosexual twin female could be due to transfer of H-Y antigen to female fetus when hematopoietic tissue and cell interchange after vascular anastomoses during fetus period ( Niku et al, 2007 ; Abuelo, 2009 ; Kozubska-Sobocińska, Danielakczech & Rejduch, 2016 ). It has been reported that H-Y antigen is activated during the formation of testes rather than triggering the formation ( Wolf, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current results indicate that slight H-Y antigen would not hamper reproduction of a heterosexual twin female. The presence of H-Y antigen in fertile heterosexual twin female could be due to transfer of H-Y antigen to female fetus when hematopoietic tissue and cell interchange after vascular anastomoses during fetus period ( Niku et al, 2007 ; Abuelo, 2009 ; Kozubska-Sobocińska, Danielakczech & Rejduch, 2016 ). It has been reported that H-Y antigen is activated during the formation of testes rather than triggering the formation ( Wolf, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that 82–97% of bovine females from heterosexual twins are freemartin and contain XX/XY chimera ( Zhang et al, 1994 ; Fujishiro et al, 1995 ; Esteves, Båge & Payan-Carreira, 2012 ; Kozubska-Sobocińska, Danielakczech & Rejduch, 2016 ). The twinning rate is rising in last few years ( Szczerbal et al, 2014 ) and it is expected that the number of fertile heterosexual twin female is also increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Triwalent zazwyczaj prawidłowo segreguje, czego efektem jest powstawanie dwóch rodzajów gamet: z prawidłową liczbą chromosomów (n = 30) oraz zawierających chromosom translokowany (n = 29) (28,42,44). Nieprawidłowa segregacja zachodzi rzadko i dotyczy kilku procent komórek dzielących się mejotycznie, a jej efektem jest powstawanie aneuploidalnych gamet (około 2,76% niezbalansowanych plemników i 4,6% niezbalansowanych oocytów), które po zapłodnieniu odpowiadają za powstawanie aneuploidalnych zarodków zamierających we wczesnym okresie rozwoju embrionalnego, co prowadzi do niewielkiego obniżenia płodności na poziomie około 5-10% (15,22). Najczęściej diagnozowaną w populacji bydła fuzją centryczną jest translokacja Robertsonowska 1;29.…”
Section: Artykuł Przeglądowy Reviewunclassified
“…Liczne badania bliźniąt bydlęcych wykazały, że na ogół buhaje z chimeryzmem leukocytarnym 60,XX/60,XY charakteryzują się parametrami płodności, jakości nasienia i jego przydatności do mrożenia, nie odbiegającymi od ogól-nie przyjętych norm i w związku z tym takie buhajki można warunkowo dopuścić do rozrodu. Z drugiej strony, szereg innych doniesień sugeruje obniżenie wskaźników płodności takich buhajów, z uwzględnie-niem wskaźnika niepowtarzalności rui i parametrów nasienia (15). Ocena jakości nasienia, prowadzona w oparciu o badania ejakulatów uzyskanych od buhajów o kariotypie 60,XX/60,XY, ujawniła istotne lub wysoko istotne obniżenie objętości ejakulatu, ruchliwości i koncentracji plemników, wyższy procent plemników uszkodzonych (wady morfologiczne głów-ne i podrzędne) oraz większą częstość występowania zmian degeneracyjnych w strukturze jąder, niekiedy azoospermię i słabe libido (30).…”
Section: Artykuł Przeglądowy Reviewunclassified
“…Given that gonadal differentiation begins earlier in male than in female fetuses [ 9 ], sex-determining hormones from the male co-twin can move to the female fetus and suppress the normal development of female reproductive organs [ 9 17 ], as well as produce other morphological changes [ 7 ]. Thus, heterosexual twin pregnancies can avoid the freemartinism phenomena when placental anastomoses fail to fuse or when fusion occurs following the critical period of reproductive organ differentiation [ 9 ]. The incidence of freemartinism in female calves born as a co-twin to male calves is high (> 90%) [ 9 19 ], whereas little is known about this congenital disorder in sheep.…”
mentioning
confidence: 99%